Strategi Brand Portfolio Untuk Perusahaan Menengah: Studi Kasus Pada Lifestyle Brand - Saputri, Marheni Eka; Swasty, Wirania; Nastiti, Nisa Eka; Utami, Fitriani Nur; Sabrina, Keysia Shafa (Universitas Diponegoro, 2024)
The lifestyle brand industry is highly competitive, with many brands competing for consumer attention and loyalty. This study aims to: 1) understand the adoption of the company's existing brand management, and 2) determine the optimal number of brands a company should own. Qualitative data were collected through in-depth interviews with key stakeholders, such as the co-founder, to understand the company's brand management practices. Secondary data in document reviews were used to assess the optimal number of brands. Based on the interviews, the company adopted the House of Brands and Sub-Branding strategies. From the document review, it was revealed that companies in the lifestyle brand industry in Indonesia tend to diversify their portfolios and expand product categories to reach various market segments and respond to trends. Having multiple brands provides flexibility in marketing strategies, positioning, and growth potential, which supports the overall development of the company.Industri lifestyle brand sangat kompetitif, dengan banyak merek bersaing untuk mendapatkan perhatian dan loyalitas konsumen. Penelitian ini bertujuan untuk: 1) mengetahui adopsi manajemen merek eksisting perusahaan saat ini, dan 2) menentukan jumlah merek optimal yang sebaiknya dimiliki perusahaan. Data kualitatif dikumpulkan melalui wawancara mendalam dengan pemangku kepentingan utama, seperti co-founder, untuk memahami praktik manajemen merek perusahaan. Data sekunder berupa review dokumen digunakan untuk meninjau jumlah merek optimal. Berdasarkan wawancara, perusahaan mengadopsi strategi House of Brands dan Sub-Branding. Dari document review, terungkap perusahaan-perusahaan dalam industri lifestyle brand di Indonesia cenderung melakukan diversifikasi portofolio dan ekspansi kategori produk untuk menjangkau berbagai segmen pasar serta merespons tren. Memiliki banyak merek memberikan fleksibilitas dalam strategi pemasaran, positioning, dan potensi pertumbuhan yang mendukung keseluruhan perkembangan perusahaan.